Influence of the annealing atmosphere on structural, optical and magnetic properties of Co-doped ZnO microrods - Aksu, S.; Bacaksiz, E.; Yilmaz, S.; Polat, I.; Altunbas, M.; Turksoy, M.; Topkaya, R.; Ozdogan, K. (ELSEVIER SCIENCE BV, 2012)
We have investigated the effects of annealing in vacuum and oxygen atmosphere at 500 degrees C on the structural, optical and magnetic properties of Co-doped ZnO microrods deposited by a spray pyrolysis method on glass substrates. The stoichiometry of the as-deposited films was determined as Zn0.91Co0.09O using X-ray photoelectron spectroscopy. X-ray diffraction pattern of the as-deposited and annealed films exhibited wurtzite crystal structure with a strong (0 0 2) preferred orientation. Surface morphology of the films obtained by scanning electron microscopy revealed that as-deposited Zn0.91Co0.09O films had hexagonal shaped rods with submicron size diameter and no significant changes were detected in the rod morphology and rod diameters with annealing. Photoluminescence and X-ray diffraction results showed a better crystalline quality obtained with the post-treatment in oxygen compared to that in vacuum. Annealing in vacuum enhanced the room temperature magnetization, which might be associated with the increased amount of oxygen vacancies created due to the out-diffusion of oxygen atoms, during the post-treatment in vacuum. Measurements at a constant magnetic field of 1 kOe in the temperature range 10-300 K showed a higher magnetization and a higher rate of increase in magnetization with decreasing temperatures for the vacuum-annealed sample compared to as-deposited and oxygen-annealed sample. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.
Keywords: ROOM-TEMPERATURE FERROMAGNETISM; SPRAY-PYROLYSIS METHOD; THIN-FILMS; SEMICONDUCTING OXIDES; ZN1-XCOXO NANOWIRES; MICROSTRUCTURE; DEPOSITION; NANOBELTS; RODS; Science & Technology - Other Topics; Physics